Synergistic Effects of Resistin and Visfatin as Adipocyte Derived Hormones on Telomerase Gene Expression in AGS Gastric Cancer Cell Line - Masoumeh Mohammadi; Nosratollah Zarghami; Mehdi Hedayati; Sara Ghaemmaghami (Acta Medica Iranica, 2017)
Recently suggested that adipocytokines may play a role in pathogenesis and progression of certain cancers, especially in gastric cancer. The previous study showed Resistin and Visfatin, as adipocyte derived hormones, separately increases telomerase (hTERT) gene, the aim of this study is investigating synergic effects of Resistin and Visfatin on telomerase gene expression, in AGS gastric cancer cell line. In this study, human gastric cancer AGS cell line was selected. After stimulation with increasing concentrations of Resistin and Visfatin recombinant proteins for 24 and 48 hours, cell proliferation was assessed by XTT assay. In order to investigate the telomerase gene expression affected by these proteins, total RNA was extracted, cDNA was synthesized, and expression of hTERT mRNA was carried out by real-time reverse transcription polymerase chain reaction. After Resistin and Visfatin, recombinant proteins treatment was increased the gastric cell line proliferation and expression of Human Telomerase Reverse Transcriptase (hTERT), but co-stimulation with Resistin and Visfatin showed greater inducible effects on cell proliferation and telomerase gene expression in comparison with the stimulatory effect of the individual hormone. This study has shown Resistin, and Visfatin synergistically increased gastric cancer cell proliferation and enhanced the telomerase gene expression. These data showed that these two hormones in gastric cancer tissue could cooperatively accelerate cancer cell growth via enhancing the telomerase expression as a cancer gene.